Intracranial haemodynamics during attenuated responses to electroconvulsive therapy in the presence of an intracerebral aneurysm. Issue 6 (1st June 1998) - Viguera, A; Rordorf, G; Schouten, R; Welch, C; Drop, L J
Abstract : OBJECTIVES: This report describes successful anaesthesia and electroconvulsive therapy (ECT) in a patient with an unruptured basilar artery aneurysm. ECT is associated with a hyperdynamic state characterised by arterial hypertension, tachycardia, and considerably increased cerebral blood flow rate and velocity. These responses pose an increased risk for subarachnoid haemorrhage when an intracranial aneurysm coexists. METHODS: A 54 year old woman presented for ECT. She had a 20 year history of major depression which was unresponsive to three different antidepressant drugs. There was also an unruptured 5 mm saccular aneurysm at the basilar tip, which had been documented by cerebral angiography, but its size had remained unchanged for the previous four years. After she declined surgical intervention, she gave informed consent for ECT. During a series of seven ECT sessions middle cerebral artery flow velocity was recorded by a pulsed transcranial Doppler ultrasonography system. She was pretreated with 50 mg oral atenolol daily, continuing up to the day of the last ECT and immediately before each treatment, sodium nitroprusside was infused at a rate of 30 μg/min, to reduce systolic arterial pressure to 90–95 mm Hg. RESULTS: Systolic flow velocity during the awake state ranged from 62–75 cm/s, remaining initially unchanged with sodium nitroprusside infusion. After induction of anaesthesia (0.5 mg/kg methohexitone and 0.9 mg/kg succinylcholine), flow velocities decreased to 39–54 cm/s, reaching maximal values of 90 cm/s (only 20% above baseline) after ECT. These flow velocities recorded post-ECT were considerably below the more than twofold increase recorded when no attenuating drugs were used. Systolic arterial blood pressure reached maximal values of 110–140 mm Hg and heart rate did not exceed 66 bpm. Rapid awakening followed each treatment, no focal or global neurological signs were apparent, and the patient was discharged in remission. CONCLUSION: In a patient with major depression and a coexisting intracerebral saccular aneurysm who was treated with ECT, the combination of β blockade with atenolol and intravenous infusion of sodium nitroprusside prevented tachycardia and hypertension, and greatly attenuated the expected increase in flow velocity in the middle cerebral artery.